ANALISIS TINGKAT PENGETAHUAN DAN SIKAP REMAJA TERHADAP PERILAKU MEROKOK DI SMP X - Rizma Aulya; Chahya Kharin Herbawani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The problem of smoking behavior among adolescents is currently a serious problem. The results from the 2018 Riskesdas data show that cigarette consumption among school-age adolescents with a prevalence of smokers aged >10 years was found to continue to increase from 2016 to 2018. The increase was 8.8% in 2016 to 9.1% in 2016. 2018. This literature review aims to determine and analyze whether the knowledge and attitudes of adolescents affect smoking behavior. The research design used in this study is a literature review by looking for several previous research journal articles that have been published through an electronic database. The number of journals analyzed in this study were 12 journals using databases from Google Scholar and Portal Garuda. The articles selected were using inclusion criteria such as full text, publications for the last 5 years, Indonesian language, open access, and research in Indonesia. Based on several research results, it was found that research between smoking attitudes and behavior in several studies showed that there was a relationship. In contrast to the research between the level of knowledge and smoking behavior, there are two studies that show that there is no relationship but there are also other studies which state that there is a relationship. The results of several journals state that in addition to knowledge and attitudes, there are other factors that can influence smoking behavior in adolescents, namely predisposing factors, enabling factors and driving factors.   Keywords         : Adolescents, Knowledge, Attitudes and Smoking Behavior